PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CONCEPT SENTENCE UNTUK MENINGKATKAN KREATIVITAS DAN KETERAMPILAN MENULIS TEKS EKSPLANASI - Desismi Hartini (DIADIK, 2024)
This study aims to (1) describe the application of the Concept Sentence Type Cooperative Learning model to improve students' creativity, (2) describe the implementation of the Concept Sentence Type Cooperative Learning model to improve explanatory text writing skills, (3) the effectiveness of the implementation of the Concept Sentence Type Cooperative learning model for improve news text writing skills. This research was conducted using Classroom Action Assessment (CAR) and quasi-experimental. The data collection method in this research uses an observation sheet to measure the teacher's ability to apply the Concept Sentence Type Cooperative model and students' creativity, as well as a test to measure students' writing text skills. For data analysis used analysis of the average score and t-test based on the results of research that has been carried out in three cycles in class XI MIPA 1 the research results in the following conclusions: (1) The application of the Concept Sentence Type Cooperative Learning Model can increase students' creativity, (2 ) The application of the Concept Sentence Type Cooperative Learning Model can improve students' explanatory text writing skills, (3) The Concept Sentence Type Cooperative Learning Model implementation effectively improves students' explanatory text writing skills in Indonesian subjects